STRATEGI GURU DALAM PENERAPAN E-BOOK INTERAKTIF UNTUK MENSTIMULASI KECERDASAN NATURALIS ANAK - Aphina Wulan Kunanti; Yuni Mauliza; Lina Amelia; Uratun Aini; Putri Ramadhani; Maya Rosita Urza (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Teachers’ strategies in utilizing digital media have become an important aspect of early childhood education in the technology-driven era. The appropriate use of digital media not only enhances engaging learning experiences but also supports various aspects of children’s development, including naturalistic intelligence. This study aims to analyze teachers’ strategies in implementing interactive e-books to stimulate young children’s naturalistic intelligence. The study employed a Systematic Literature Review (SLR) method by analyzing 10 national journal articles published between 2021 and 2026 that were relevant to the research topic. The review process involved the stages of identification, selection, evaluation, and synthesis of findings from studies that met the inclusion criteria. The results indicate that teachers’ strategies include selecting environment-based content, facilitating technology-assisted nature exploration, optimizing interactive features, implementing thematic learning approaches, evaluating children’s development, and collaborating with parents in supporting the use of digital media. The findings further reveal that interactive e-books have the potential to improve children’s observation skills, classification abilities, recognition of living organisms’ characteristics, and environmental awareness. In addition, visual, audio, animation, and interactive activities embedded in e-books contribute to increasing children’s engagement and learning motivation. This review provides practical implications for early childhood educators in meaningfully integrating educational technology to support the development of children’s naturalistic intelligence. The findings may also serve as a reference for educational media developers and future researchers in designing digital learning innovations that align with the developmental characteristics of young children.